A Critical Analysis of the Debate on State Failure in Africa (Global Journal of Human-Social Science, 2016)
The focus of this study is to critically examine the Western debate on State failure in Africa Western research Institutes and Agencies such as the Freedom House Annual Survey the Fund for Peace Index and the World Bank Governance Matters have come to the conclusion that most African States have failed in the discharge of their statutory responsibilities This is because they are unable and incapable of sustaining democratic institutions and protecting the lives and property of their citizens As a qualitative research data collected was through primary and secondary sources The primary sources included discussions and interviews while the secondary sources was literature review Newspapers official Bulletins and magazines It was discovered that the State failure debate did not take into consideration Africa s Colonial and neo- Colonial experiences Also the policy implication of this project is to ensure that the continent s political economy is within the control of the global capitalist system We therefore recommend that African leaders should not be bothered about this development but be concerned about the provision of good governance and human security
Keywords: human security; state failure; global capitalist system; colonialism; prebendalism